Adsorption of 2,4,6-trichlorophenol on kaolinite: DFT calculations - Sara Ghezali; Amina Mahdad-Benzerdjeb (Graduate Program of Syiah Kuala University, 2017)
The aim of this work is to explore the adsorption process of an organic pollutant the 2,4,6-trichlorophenol on the clay mineral (kaolinite) surface in order to identify the sites of adsorption as well as conformations corresponding to the lowest energies. Ab-initio calculations have been used to investigate the adsorption process using a representative cluster model. According to the results obtained on the various studied models, the orientation of TCP on the surfaces clay affect the parameters such as : HOMO-LUMO energy gap, the enthalpy change (ΔH), the thermal Gibbs free energy (ΔG) and entropy contribution (ΔS). The results point out a preferential adsorption of TCP on the octahedral surface and the NBO analysis indicates that the electron donor-acceptor complex was the dominant adsorption mechanism.